Preparation method of ovalbumin / tannic acid-lithium clay nanocomposite film

CN122958729APending Publication Date: 2026-10-23THE PEOPLES HOSPITAL WEIFANG CITY CN0
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611022079.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明所要解决的技术问题是:第一,现有蛋白质基纳米复合膜的稳定性差,难以满足长期使用需求;第二,现有蛋白质基纳米复合膜的制备过程复杂繁琐,涉及大量有机溶剂和化学试剂;第三,现有蛋白质基纳米复合膜难以按需制备,在实际应用中推广困难

Benefits of technology

[0032]1)纳米复合膜的稳定性高

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958729A_ABST
    Figure CN122958729A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of an egg white / tannic acid-halloysite nanocomposite film, which comprises the following steps: dispersing halloysite in egg white, and anchoring tannic acid around the halloysite through the intermolecular interaction between the tannic acid and the egg white, so as to obtain a uniformly dispersed egg white / tannic acid-halloysite composite system; and drying the composite system to form a stable egg white / tannic acid-halloysite nanocomposite film. The method can be used for preparing nanocomposite films with required sizes in a full aqueous phase system according to requirements, and has the advantages of green environmental protection, simplicity, easy operation and low cost. The prepared nanocomposite film has excellent stability, interfacial adhesion, flame retardant performance and chemical corrosion resistance, and can be widely applied to the surface protection of various substrates such as high polymer materials, metal materials, inorganic non-metal materials and wooden products, and has a wide industrial application prospect in the fields of flame retardant coatings and chemical corrosion resistant protective coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of protein-based functional materials, specifically relating to a method for preparing an ovalbumin / tannic acid-lithium diatomite nanocomposite membrane. Background Technology

[0002] Protein-based nanocomposite membranes use natural biomaterials as raw materials, are completely free of toxic and harmful substances, and require no organic solvents or other harmful chemicals, thus possessing high environmental friendliness and sustainability. Furthermore, proteins are rich in various functional groups; by altering their structure or adding functional modifying groups, protein-based nanocomposite membranes can be regulated to achieve multiple functions, such as flame retardancy, antifouling, and corrosion resistance, thus showing broad application prospects in the field of functional coating materials.

[0003] Currently, the main methods for preparing protein thin film coatings include physical spraying, chemical cross-linking, and covalent bonding. However, these existing technologies still have many shortcomings in practical applications: First, the stability of existing protein-based membranes is low, and they are easily affected by environmental factors (such as temperature, humidity, and pH) and their performance deteriorates; second, the use of large amounts of chemical reagents easily generates byproducts, causing environmental pollution and health damage, which does not meet the requirements of green chemistry development; third, the high cost of proteins themselves limits their large-scale production and application; fourth, the durability of existing membranes is poor, and their performance will significantly decline during long-term use, making it difficult to meet the needs of practical applications.

[0004] To address the aforementioned issues, there is an urgent need to develop a protein-based nanocomposite membrane with high stability, simple preparation process, green and environmentally friendly characteristics, and controllable cost, as well as its preparation method. Summary of the Invention

[0005] The technical problems to be solved by this invention are: first, the stability of existing protein-based nanocomposite films is poor, making it difficult to meet the requirements of long-term use; second, the preparation process of existing protein-based nanocomposite films is complex and cumbersome, involving a large number of organic solvents and chemical reagents; third, existing protein-based nanocomposite films are difficult to prepare on demand, making it difficult to promote them in practical applications.

[0006] To address the aforementioned technical problems, this invention provides a method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane. The method involves first uniformly dispersing lithium diatomaceous earth using ovalbumin, and then anchoring tannic acid around the lithium diatomaceous earth using the intermolecular interactions between tannic acid and ovalbumin, thereby obtaining a uniformly dispersed ovalbumin / tannic acid-lithium diatomaceous earth composite system. After drying, a stable ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane is formed. This nanocomposite membrane exhibits excellent stability and can firmly adhere to the surface of various substrate materials.

[0007] Specifically, the present invention provides a method for preparing an ovalbumin / tannic acid-lithium diatomite nanocomposite membrane, comprising the following steps:

[0008] Step 1: Preparation of ovalbumin-lithium diatomaceous earth mixture

[0009] S1: An ovalbumin solution is prepared by dissolving ovalbumin and glycerol in deionized water; the concentration of ovalbumin in the solution is 10 mg / mL to 30 mg / mL, and the concentration of glycerol in the solution is 10 mg / mL to 30 mg / mL.

[0010] S2: Disperse lithium diatomite in water to prepare a lithium diatomite dispersion; the concentration of the lithium diatomite dispersion is 2 mg / mL to 8 mg / mL;

[0011] S3: Prepare an ovalbumin-lithium diatomaceous earth mixture by mixing the ovalbumin solution with the lithium diatomaceous earth dispersion; stir and mix at room temperature for 3-12 h.

[0012] Step 2: Preparation of tannic acid solution

[0013] Tannic acid is dissolved in water to prepare a tannic acid solution; the concentration of tannic acid in the solution is 2 mg / mL to 4 mg / mL.

[0014] Step 3: Preparation of ovalbumin / tannic acid-lithium diatomaceous earth mixture

[0015] The tannic acid solution was added to the ovalbumin-lithium diatomite mixture to prepare an ovalbumin / tannic acid-lithium diatomite mixture; the mixture was stirred at room temperature for 12-24 h.

[0016] Step 4: Film Formation

[0017] The ovalbumin / tannic acid-lithium diatomaceous earth mixture was dried alone or together with the substrate material at 30-50°C for 12-24 h to obtain an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane.

[0018] As a preferred embodiment of the present invention, the concentration of ovalbumin in the ovalbumin solution in step one is 20 mg / mL.

[0019] As a preferred embodiment of the present invention, the concentration of glycerol in the ovalbumin solution in step one is 20 mg / mL.

[0020] As a preferred embodiment of the present invention, the concentration of the lithium diatomite dispersion in step one is 6 mg / mL.

[0021] As a preferred embodiment of the present invention, the concentration of the tannic acid solution in step two is 3 mg / mL.

[0022] As a preferred embodiment of the present invention, the stirring and mixing time in step one is 6 hours.

[0023] As a preferred embodiment of the present invention, the mixing time in step three is 18 hours.

[0024] As a preferred embodiment of the present invention, the drying temperature in step four is 40°C and the drying time is 18 h.

[0025] The lithium diatomite (LAP) described in this invention is a synthetically produced lithium magnesium silicate (sodium magnesium silicate) nanomaterial that readily disperses in water to form a transparent gel under stirring conditions. The surface of the lithium diatomite nanosheets is rich in hydroxyl groups, which can bind to protein molecules through hydrogen bonding, thus achieving a physical cross-linking effect.

[0026] The substrate material includes polymer materials, metallic materials, inorganic non-metallic materials, and wood products. The polymer materials include, but are not limited to, polyurethane (PU), polyethylene (PE), polymethyl methacrylate (PMMA), polypropylene (PP), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), polystyrene (PS), and paraffin film; the metallic materials include, but are not limited to, aluminum (Al), titanium (Ti), and iron (Fe); the inorganic non-metallic materials include, but are not limited to, glass and silicon (Si); and the wood products include, but are not limited to, paper, leaves, and wood.

[0027] The present invention also provides an ovalbumin / tannic acid-lithium diatomite nanocomposite membrane prepared by the above preparation method.

[0028] The present invention relates to an ovalbumin / tannic acid-lithium diatomite nanocomposite membrane with lithium diatomite nanosheets. Due to its ability to form a stable inorganic barrier structure during heating, this membrane, in synergy with the dense composite network formed by ovalbumin / tannic acid, effectively hinders heat transfer, reduces the contact between combustible components and oxygen, and delays the thermal decomposition and combustion process of the substrate, thereby improving the flame retardant performance of the material. Simultaneously, the nanocomposite membrane exhibits a stable structure, continuous coverage, and strong interfacial bonding, maintaining good integrity in acidic, alkaline, and organic solvent environments. It also provides a certain barrier against the penetration of external corrosive media, thereby improving the chemical corrosion resistance and service stability of the protected material. Therefore, it can be used as a highly efficient flame-retardant and chemically resistant protective membrane material.

[0029] Therefore, the present invention further provides the application of the ovalbumin / tannic acid-lithium diatomite nanocomposite membrane as a flame-retardant and / or chemically resistant protective membrane material.

[0030] The present invention also provides a flame-retardant and / or chemical corrosion-resistant protection method, comprising the step of covering the surface of the substrate to be protected with the ovalbumin / tannic acid-lithium diatomite nanocomposite film.

[0031] The ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane and its preparation method provided by this invention have the following beneficial effects:

[0032] 1) High stability of nanocomposite membranes

[0033] The OVA / TA-LAP dispersion of this invention can maintain a relatively stable state for a long period (30 days). The OVA / TA-LAP nanocomposite coating film exhibits significant advantages in mechanical properties and structural stability. In the formation process of the OVA / TA-LAP nanocomposite coating film, OVA / TA acts as the "slurry," while LAP acts as the "bricks." OVA / TA is first adsorbed around the LAP nanosheet structure through electrostatic interactions. Subsequently, during the formation of the nanocomposite coating film, the water in the entire system gradually disappears, and the concentration of the remaining "slurry" increases. The forces between the slurries and between the slurry and LAP also gradually increase, which not only promotes the close arrangement of LAP but also greatly improves the mechanical strength of the entire nanocomposite coating film.

[0034] 2) Nanocomposite films can adhere firmly to the surface of various substrate materials.

[0035] The average peel strength of the OVA / TA-LAP nanocomposite coating film of this invention is close to 700 N / m on the surfaces of polymers, inorganic materials, metals and natural materials, indicating that the nanocomposite coating film of this invention has strong interfacial bonding with various substrates and can firmly adhere to the surface of various substrate materials.

[0036] 3) The preparation process of nanocomposite membranes is green, environmentally friendly, simple and easy to carry out.

[0037] The preparation process of the OVA / TA-LAP nano-coating membrane of this invention is simple, the reaction conditions are mild, the entire process is carried out in an all-aqueous system, and no waste gas, waste liquid or solid waste residue is generated, and there are no toxic by-products; the entire production process is clean and pollution-free, meeting the requirements of green, energy-saving and environmental protection.

[0038] 4) The preparation cost of nanocomposite films is relatively low.

[0039] The raw materials used in this invention, ovalbumin, tannic acid, and lithium diatomite, are all widely available and low-cost natural or synthetic materials. They do not require expensive chemical reagents and complex equipment, which is conducive to large-scale production and application.

[0040] 5) Nanocomposite membranes of specific sizes can be customized as needed.

[0041] The ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane of this invention exhibits excellent substrate compatibility and interfacial adhesion, enabling the formation of a continuous, stable, and non-detachable protective layer on substrates of varying materials, shapes, and sizes. The nanocomposite membrane's film area, thickness, and coverage method can be adjusted as needed based on the size, surface morphology, and protection requirements of the actual application, achieving customized coating for planar, curved, and irregular surfaces. Therefore, the nanocomposite membrane of this invention can adapt to the flame-retardant and chemical corrosion-resistant protection requirements of different application scenarios, possessing good application flexibility and promotional value.

[0042] 6) Nanocomposite membranes have good adaptability and flexibility.

[0043] The OVA / TA-LAP nanocomposite coating film of this invention exhibits excellent adaptability, flexibility, and coverage, enabling it to form a uniform coating layer on substrates of various types and complex shapes. The surface morphology of the nanocomposite coating film is consistent across different substrates, all displaying smooth and continuous characteristics, demonstrating its significant advantage in adapting to complex environments.

[0044] 7) The nanocomposite film has excellent flame retardant properties.

[0045] Lithium diatomite nanosheets can form a stable inorganic barrier structure during heating. In synergy with the dense composite network composed of ovalbumin / tannic acid, they can effectively hinder heat transfer, reduce the contact between combustible components and oxygen, and delay the thermal decomposition and combustion process of the substrate, thereby improving the flame retardant performance of the material.

[0046] 8) The nanocomposite film has excellent chemical corrosion resistance.

[0047] The nanocomposite membrane of this invention has a stable structure, continuous coverage, and strong interfacial bonding. It can maintain good integrity in chemical environments such as acidic, alkaline, and organic solvents, and has a certain barrier effect against the penetration of external corrosive media, thereby improving the chemical corrosion resistance and service stability of the protected material. Attached Figure Description

[0048] Figure 1 This is a photograph of an ovalbumin / tannic acid-lithium diatomite nanocomposite membrane.

[0049] Figure 2 This is a photograph of an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite film adhering to the surface of various materials.

[0050] Figure 3 Formation and characterization of ovalbumin / tannic acid-lithium diatomite nanocomposite membrane system. (a) ZETA potential of the dispersion; (b) Particle size distribution of the dispersion measured by dynamic light scattering.

[0051] Figure 4 Changes in the secondary structure of ovalbumin (OVA) after the addition of lithium diatomaceous earth LAP. (a) Fourier transform infrared spectra of OVA, LAP, OVA-LAP, and OVA / TA-LAP; (b) 800-1200 cm⁻¹ -1 (c) Circular dichroism curves of OVA, LAP, OVA-LAP and OVA / TA-LAP; (d) Changes in the content of secondary structure of OVA.

[0052] Figure 5 The results of ThT staining of ovalbumin (OVA) after the addition of lithium diatomaceous earth LAP. (a) Fluorescence spectra of ThT after co-incubation with OVA, LAP, OVA-LAP and OVA / TA-LAP, (b) Fluorescence micrograph of OVA / TA-LAP after ThT staining.

[0053] Figure 6 Peeling force determination of OVA / TA-LAP: The figure shows the force required to peel OVA-LAP and OVA / TA-LAP nanocomposite film from different substrate materials. Each experiment was repeated 3 times.

[0054] Figure 7 Nanoindentation test of OVA / TA-LAP nanocomposite membranes. (a) Force-displacement curves of 2 mg / mL LAP nanocomposite membranes; (b) Force-displacement curves of 4 mg / mL LAP nanocomposite membranes; (c) Force-displacement curves of 6 mg / mL LAP nanocomposite membranes; (d) Force-displacement curves of 8 mg / mL LAP nanocomposite membranes.

[0055] Figure 8 Young's modulus of OVA / TA-LAP nanocomposite membrane.

[0056] Figure 9 Energy dispersive X-ray diffraction analysis of the substrate surface after OVA / TA-LAP nanocomposite film coating.

[0057] Figure 10 XPS spectra of OVA / TA-LAP nanocomposite films on different substrate surfaces before and after formation. (a) Full spectrum of aluminum sheet before and after nanocomposite film formation; (b) High-resolution O1s spectrum of bare aluminum sheet; (c) High-resolution O1s spectrum of coated aluminum sheet; (d) Full spectrum of polyurethane before and after nanocomposite film formation; (e) High-resolution O1s spectrum of bare polyurethane; (f) High-resolution O1s spectrum of coated polyurethane; (g) Full spectrum of silicon wafer before and after nanocomposite film formation; (h) High-resolution O1s spectrum of bare silicon wafer; (i) High-resolution O1s spectrum of coated silicon wafer.

[0058] Figure 11 SEM images of OVA / TA-LAP nanocomposite films on different substrate materials, scale bar 10 μm.

[0059] Figure 12 Atomic force microscopy images of OVA / TA-LAP nanocomposite films at different LAP concentrations. (a) 2 mg / mL LAP; (a') Surface roughness analysis of 2 mg / mL LAP nanocomposite film; (b) 8 mg / mL LAP; (b') Surface roughness analysis of 8 mg / mL LAP nanocomposite film; (c) Magnified view of 8 mg / mL LAP nanocomposite film; (c') Particle size analysis of 8 mg / mL LAP nanocomposite film.

[0060] Figure 13 Microstructure of OVA / TA-LAP nanocomposite film. (a) SEM cross-sectional image of OVA-LAP film; (b) SEM cross-sectional image of OVA / TA-LAP nanocomposite film; scale bar is 5 μm; (c) XRD patterns of OVA, LAP, OVA-LAP and OVA / TA-LAP; (d) Enlarged XRD patterns of OVA, LAP, OVA-LAP and OVA / TA-LAP.

[0061] Figure 14 TEM images of LAP and OVA / TA-LAP. (a) OVA / TA-LAP; (b) LAP; (c) magnified view of OVA / TA-LAP; (d) energy spectrum of OVA / TA-LAP.

[0062] Figure 15 Static contact angle experiment of OVA / TA-LAP nanocomposite film. (a) Photograph of water droplets on the surface of the substrate material; (b) Statistical analysis of the static contact angle of the substrate before and after the formation of OVA / TA-LAP nanocomposite film; (c) Hydrophilicity analysis of the surface of OVA / TA-LAP nanocomposite film.

[0063] Figure 16 Degradation of OVA / TA-LAP nanocomposite membranes in different solvents. (a) Shape differences of OVA / TA-LAP nanocomposite membranes after one week in different solvents; (b) Mass changes of nanocomposite membranes in different solvents; (c) Schematic diagram of the stability of OVA / TA-LAP nanocomposite membranes.

[0064] Figure 17High-temperature resistance of OVA / TA-LAP nanocomposite membranes. (a) Horizontal combustion test of i. paraffin film and ii. paraffin film after OVA / TA-LAP coating; (b) Vertical combustion test of i. paraffin film and ii. paraffin film after OVA / TA-LAP coating. The dimensions of the paraffin film in the figure are all 3 cm (length) × 1 cm (width); (c) Thermogravimetric curves of paraffin film before and after OVA / TA-LAP nanocomposite membrane coating; (d) Thermogravimetric curves of nanocomposite membranes with different lithium diatomite concentrations. Detailed Implementation

[0065] The present invention will be further described below with reference to specific embodiments. Unless otherwise specified, the reagents, materials, instruments, and methods used in the present invention are conventional reagents, materials, instruments, and methods in the art, and unless otherwise specified, the reagents, materials, and instruments are all commercially available products in the art.

[0066] Example 1: Preparation of self-supporting ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane

[0067] The ovalbumin used in this embodiment is egg white ovalbumin with a molecular weight of 44.5 kDa; glycerol has a molecular weight of 92.09; tannic acid has a molecular weight of 1701.2; and lithium diatomaceous earth nanoparticles have a size of 20-30 nm; all of which are commercially available products.

[0068] Step 1: Preparation of ovalbumin-lithium diatomaceous earth mixture

[0069] S1: An ovalbumin solution is prepared by dissolving ovalbumin and glycerol in deionized water; the concentration of ovalbumin in the solution is 10 mg / mL to 30 mg / mL, and the concentration of glycerol in the solution is 10 mg / mL to 30 mg / mL.

[0070] S2: Disperse lithium diatomite in water to prepare a lithium diatomite dispersion; the concentration of the lithium diatomite dispersion is 2 mg / mL to 8 mg / mL;

[0071] S2: Prepare an ovalbumin-lithium diatomaceous earth mixture by mixing the ovalbumin solution with the lithium diatomaceous earth dispersion; stir and mix at room temperature for 3-12 h.

[0072] Step 2: Preparation of tannic acid solution

[0073] A tannic acid solution is prepared by dissolving tannic acid in water; the concentration of tannic acid in the solution is 2 mg / mL to 4 mg / mL.

[0074] Step 3: Preparation of ovalbumin / tannic acid-lithium diatomaceous earth mixture

[0075] The tannic acid solution was added to the ovalbumin-lithium diatomite mixture to prepare an ovalbumin / tannic acid-lithium diatomite mixture; the mixture was stirred at room temperature for 12-24 h.

[0076] Step 4: Place the ovalbumin / tannic acid-lithium diatomaceous earth mixture in a flexible polytetrafluoroethylene mold and dry it at 30-50℃ for 12-24 h to obtain a self-supporting ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane (OVA / TA-LAP membrane). Figure 1 As shown.

[0077] Table 1. Formulation of self-supporting ovalbumin / tannic acid-lithium diatomite nanocomposite membrane

[0078] 1 10 10 2 2 30 ℃,24 h 656.33 2 10 10 4 3 40 ℃,20 h 1136.86 3 10 10 8 4 50 ℃,12 h 1981.46 4 20 20 2 2 30 ℃,20 h 681.92 5 20 20 4 3 40 ℃,12 h 1288.35 6 20 20 8 4 50 ℃,24 h 2036.71 7 30 30 2 2 30 ℃,12 h 724.18 8 30 30 4 3 40 ℃,24 h 1342.69 9 30 30 8 4 50 ℃,20 h 2098.54

[0079] Example 2: Ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membranes with different substrates

[0080] Ovalbumin / tannic acid-lithium diatomite nanocomposite membranes were prepared on different substrates. Steps one to three were exactly the same as in Example 1, except that in step four, the ovalbumin / tannic acid-lithium diatomite mixture was dried together with the substrate material at 30-50°C for 12-24 h to obtain the ovalbumin / tannic acid-lithium diatomite nanocomposite membrane. Figure 2 As shown.

[0081] The substrate materials include polymeric materials such as polyurethane (PU), polyethylene (PE), polymethyl methacrylate (PMMA), polypropylene (PP), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), polystyrene (PS), and paraffin film; metallic materials such as aluminum (Al), titanium (Ti), and iron (Fe); inorganic non-metallic materials such as glass and silicon (Si); and wood products such as paper, leaves, and wood.

[0082] Table 2. OVA / TA-LAP nanocomposite films on different substrates

[0083] OVA / TA-LAP nanocomposite film on polymer material surface Polyurethane (PU), polyethylene (PE), polymethyl methacrylate (PMMA), polypropylene (PP), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), polystyrene (PS), paraffin film, etc. It can form continuous, uniform and stable OVA / TA-LAP nanocomposite films on the surface of different polymer materials, with good flexibility and covering ability. Used for flame retardant and chemical corrosion protection of polymer material surfaces. OVA / TA-LAP nanocomposite film on the surface of inorganic non-metallic materials Glass, silicon, etc. A relatively complete and continuous nanocomposite protective layer can be formed on the surface of inorganic non-metallic materials. Used for chemical corrosion protection of inorganic non-metallic material surfaces. OVA / TA-LAP nanocomposite film on metal material surface Aluminum (Al), titanium (Ti), iron (Fe), etc. A stable OVA / TA-LAP nanocomposite film can be formed on the surface of metal materials, effectively covering the substrate surface. Used for chemical corrosion protection of metallic material surfaces. OVA / TA-LAP nanocomposite film on wood product surface Paper, leaves, and wood, etc. It can form a uniform coating on fibrous, porous, or irregularly shaped natural materials, exhibiting good substrate adaptability. Used for the protection of natural material surfaces.

[0084] Experimental Example 3: Characterization of Ovalbumin / Tanonic Acid-Lithium Diatomite Nanocomposite Membrane (OVA / TA-LAP Membrane)

[0085] This invention provides a novel protein nanocomposite membrane, rather than simply adding lithium diatomaceous earth to an OVA / TA-LAP membrane. Through extensive research and experimentation, the inventors discovered that ovalbumin (OVA) undergoes a series of changes upon binding with lithium diatomaceous earth (LAP), resulting in a more stable and high-performance protein-based nanocomposite membrane.

[0086] (1) OVA / TA-LAP conformational changes

[0087] Lithium diatomite is a layered silicate nanosheet structure, whose main chemical components are silicon, magnesium, and lithium, and its chemical formula is [chemical formula missing]. Lithium diatomite possesses a nanoscale sheet-like structure, with each single sheet having a diameter of approximately 25-30 nm and a thickness of approximately 1 nm. Its sheet-like structure can be easily dispersed in water under stirring, forming a colorless colloidal dispersion. The OVA / TA-LAP dispersion of this invention can maintain a relatively stable state for a long period (30 days). The good dispersion and long-term stable dispersion of OVA / TA-LAP in aqueous solution is beneficial for constructing high-performance protein-based nanocomposite membranes.

[0088] During the formation of OVA / TA-LAP, the zeta potential and particle size undergo a series of changes: First, when the OVA solution is mixed with the LAP dispersion, the overall negative charge of the system is significantly enhanced. This is mainly because the OVA molecules themselves carry a negative charge, which allows them to adsorb onto the side surfaces of the LAP sheet structure through electrostatic interactions during mixing, further shielding the positive charge on the LAP surface and thus increasing the overall zeta potential. During the binding of OVA and LAP, OVA molecules bind to LAP through electrostatic interactions, resulting in a slight increase in the size of the complex. After the addition of TA, TA molecules bind to the OVA adsorbed on the side surfaces of LAP through their hydrogen bonds and hydrophobic groups. This further increases the negative charge of the entire system and also causes a further increase in the size of the complex. The addition of TA not only enhances the stability of the complex but also improves its dispersibility and anti-settling properties in water by increasing the negative charge.

[0089] The ZETA potential of LAP was -25.36 mV, with its particle size mainly distributed around 28.21 nm. The negative charge of LAP is primarily due to the large amount of negative charge on the upper and lower surfaces (25-30 nm) of its lamellar structure, while only a small amount of positive charge is present on the 1 nm side surface, resulting in an overall negative charge. When the OVA solution was mixed with the LAP dispersion, the ZETA potential of the system became -31.65 mV, and the size increased to approximately 50.75 nm. Upon the addition of tannic acid, the ZETA potential of the entire system decreased to -37.47 mV, and its size distribution also improved to 190.10 nm. Figure 3 a, Figure 3 b).

[0090] In the Fourier transform infrared spectra of OVA, LAP, OVA-LAP, and OVA / TA-LAP, 3486 cm⁻¹ -1The signal at 1648 cm⁻¹ represents the stretching vibration peak of intermolecular hydrogen bonds. When OVA and LAP form a complex system, this bond shifts towards a lower wavenumber, indicating a certain hydrogen bond interaction between OVA and LAP. -1 The signal at this point represents the stretching vibration peak of C=O in the amide I band and the in-plane bending vibration peak of CNH in the amide II band of OVA. However, when LAP is added, this peak shows a significant redshift (1654 cm⁻¹). -1 This indicates that the electrostatic interaction between OVA and LAP, as well as the formation of hydrogen bonds, led to certain changes in the protein's secondary structure. Upon the addition of TA, the peak showed a more pronounced red shift (1661 cm⁻¹). -1 This indicates that TA further induced changes in the secondary structure of OVA. Figure 4 a and Figure 4 b). 1065 cm -1 The signal at this point represents the in-plane bending vibration of CH in the substituted benzene structure. This peak was not observed in the infrared spectra of OVA and LAP, but a weak peak appeared in OVA-LAP and OVA / TA-LAP, indicating that the interaction between OVA and LAP caused a conformational change in OVA to some extent, thereby exposing more substituted benzene structures hidden inside the protein. In addition, after the addition of tannic acid, the peak value increased from 1065 cm⁻¹. -1 It became 1072 cm -1 This indicates that the addition of TA further altered the conformation of OVA, exposing more substituted benzene structures. Furthermore, in FTIR at 800-1200 cm⁻¹... -1 The absorption peaks represent the in-plane and out-of-plane vibrations of the Si-O bonds in LAP. This peak was not observed in the OVA sample, while the absorption band in OVA-LAP and OVA / TA-LAP shifted to lower wavenumbers, further confirming the existence of a certain interaction between OVA and LAP.

[0091] OVA exhibited its characteristic circular dichroism curve, while LAP did not show a characteristic peak of circular dichroism. After the OVA-LAP composite system was formed, the absorption peak of the OVA characteristic curve red-shifted, and this peak further red-shifted upon the subsequent addition of TA. Figure 4 c), indicating that the secondary structure of OVA was altered through its interaction with LAP and TA. Further analysis of the circular dichroism chromatogram results using CDNN software revealed a decrease in the α-helix content and an increase in the β-sheet content in OVA. Figure 4 d).

[0092] Thioflavin T (ThT) staining assays also confirmed changes in the secondary structure of OVA in the OVA / TA-LAP dispersion. When OVA interacted with LAP, the fluorescence intensity significantly increased (…). Figure 5 a). This indicates that the interaction between OVA and LAP leads to an increase in the β-sheet content of OVA. Upon addition of TA, the secondary structure of OVA undergoes further changes, with an even greater increase in β-sheet content, resulting in higher fluorescence emission intensity. The OVA / TA-LAP composite system stained with ThT also exhibited abundant green fluorescence signals under a fluorescence microscope. Figure 5 (b) These results are consistent with those obtained from Fourier transform infrared spectroscopy and circular dichroism spectroscopy, indicating that the formation of the nanocomposite film is accompanied by significant changes in the secondary structure of OVA, especially the increase in β-sheet content, suggesting that OVA evolves towards a more stable conformation during the formation of the OVA / TA-LAP composite.

[0093] (2) OVA / TA-LAP adhesion properties

[0094] The adhesion properties of nanocomposite films on different substrate surfaces were investigated using a 180° tape peel test. In the experiment, OVA-LAP or OVA / TA-LAP coated substrate materials (20 mm × 20 mm in size) were first fixed to a titanium plate using 3M double-sided tape. Then, the OVA / TA-LAP nanocomposite film surface was adhered to the tape using 3M double-sided tape, and a 15 kg weight was applied to fully compact the tape and ensure the elimination of residual air bubbles, thus guaranteeing good contact between the tape and the nanocomposite film. Next, the bottom of the tape was folded back 180°, and the tape was uniformly peeled from the bottom using a universal tensile testing machine at a speed of 50 mm / min.

[0095] like Figure 6 As shown, the average peel strength of the OVA / TA-LAP nanocomposite film on polymer, inorganic, metal, and natural material surfaces is close to 700 N / m. In contrast, the peel strength of the OVA-LAP nanocomposite film on the same substrate is significantly lower, only around 300 N / m. This significant difference indicates that the addition of tannic acid significantly enhances the interfacial adhesion between the nanocomposite film and various substrates.

[0096] This extremely strong interfacial adhesion is mainly due to two factors: First, TA induces a conformational change in OVA, making the OVA structure more extended and exposing more functional groups such as phenylalanine (Phe), tryptophan (Trp), tyrosine (Tyr), histidine (His), proline (Pro), arginine (Arg), lysine (Lys), and cysteine ​​(Cys). These functional groups provide abundant active binding sites, enhancing interfacial adhesion with the substrate. Second, TA itself contains a large number of phenolic hydroxyl structures, which can form strong bonds with the substrate material through hydrogen bonding, hydrophobic interactions, π-π interactions, and metal coordination, thereby enhancing the adhesion of the nanocomposite film. The strong interfacial adhesion of the OVA / TA-LAP nanocomposite film effectively solves the problem of weak adhesion of traditional nanocomposite films to substrate surfaces, providing a reliable solution for preparing stable protein-based thin films on various substrates.

[0097] (3) Mechanical properties of OVA / TA-LAP

[0098] The mechanical properties of the OVA / TA-LAP nanocomposite film were further evaluated using nanoindentation testing. Force-displacement curves of the OVA / TA-LAP nanocomposite film at different LAP concentrations were presented. With increasing LAP concentration, the maximum bearing capacity of the nanocomposite film increased significantly, indicating that the hardness of the nanocomposite film improves with increasing LAP concentration. Furthermore, the repeatability and consistency of the force-displacement curves reflect the material's uniformity. The force-displacement curves at different LAP concentrations all showed good repeatability, indicating that the prepared nanocomposite film has good uniformity. Figure 7 ad)

[0099] Further Young's modulus analysis results (such as...) Figure 8 As shown in the figure, increasing the LAP concentration significantly improves the rigidity of the nanocomposite membrane. When the LAP concentration is 2 mg / mL, the Young's modulus of the nanocomposite membrane is 656.33 MPa; when the LAP concentration increases to 8 mg / mL, the Young's modulus reaches 2000 MPa, significantly higher than other concentrations. Therefore, the Young's modulus of the OVA / TA-LAP nanocomposite membrane increases significantly with increasing LAP concentration.

[0100] This is primarily due to the "slurry-brick" structure within the OVA / TA-LAP nanocomposite membrane. At low concentrations (2 mg / mL LAP), the LAP particles in the nanocomposite membrane resemble bricks dispersed in "slurry." The relatively low LAP concentration results in fewer contact surfaces between these particles, leading to lower overall rigidity of the nanocomposite membrane, i.e., a relatively low Young's modulus at this concentration. As the LAP concentration increases to 8 mg / mL, the number of LAP particles in the nanocomposite membrane increases, forming a denser network structure, similar to a more concentrated arrangement of "bricks" in "slurry." This dense structure increases the overall Young's modulus of the membrane, reaching over 2000 MPa. At this point, the interaction and bonding between LAP particles are stronger, making the membrane more resistant to deformation under stress. In other words, the structure formed by low-concentration LAP particles is relatively loose, while the internal structure formed by high-concentration LAP particles is more dense, thus leading to an increase in its Young's modulus.

[0101] This performance improvement is primarily attributed to the introduction of LAP as a reinforcing phase in the nanocomposite film. LAP possesses high rigidity and good dispersibility, enabling it to effectively bear loads in the composite material and improve overall mechanical properties. Specifically, under the influence of the OVA / TA "slurry," the lamellar structure ("bricks") of LAP can be uniformly distributed within the composite matrix, forming a good interfacial bond, thereby increasing the material's hardness and rigidity. These results demonstrate that LAP plays a crucial role in enhancing the mechanical properties of OVA / TA-LAP nanocomposite films, providing a theoretical basis for the subsequent high stability and application of OVA / TA-LAP nanocomposite films.

[0102] (4) Surface element distribution of OVA / TA-LAP nanocomposite film

[0103] Lithium diatomite, officially known as lithium magnesium magnesium pyrophosphate tetrasodium, is primarily composed of layered silicate nanosheets. Its chemical composition includes silicon, magnesium, sodium, and lithium, and its chemical formula is [chemical formula missing]. Energy-dispersive X-ray spectroscopy (EDX) analysis showed that after the formation of the OVA / TA-LAP nanocomposite film on the substrate surface, the characteristic element distribution of the substrate material was completely covered, replaced by a uniformly distributed distribution of the OVA / TA-LAP nanocomposite film characteristic elements. For example, for a polytetrafluoroethylene (PTFE) substrate coated with an OVA / TA-LAP nanocomposite film, the original substrate characteristic element (such as chlorine) signal was completely covered, showing the characteristic elements of the nanocomposite film (…). Figure 9 Similarly, for metal substrates such as aluminum and titanium, the corresponding metal element signals disappear after coating with the nanocomposite film, which further proves the excellent coverage effect of the OVA / TA-LAP nanocomposite film on various substrate materials.

[0104] Further EDX quantitative analysis showed that the silicon, magnesium, and sodium contents in the nanocomposite film were almost identical to those of the standard lithium diatomite, indicating that the LAP nanosheets were uniformly distributed in the composite film, consistent with the distribution of the standard. The layered structure of the LAP nanosheets, even in the presence of OVA and TA, was uniformly distributed in the nanocomposite film, which is significant for performance optimization. Furthermore, lithium was not detected in the EDX data, mainly due to its low content and the energy signal being masked by the silicon and magnesium signals. Nevertheless, the uniform distribution of other elements still indicates that the OVA / TA-LAP nanocomposite film possesses good structural consistency and uniformity.

[0105] Three typical substrate materials were selected for the study: aluminum (a metallic material), polyurethane (a polymeric material), and silicon (an inorganic material). After the formation of the OVA / TA-LAP nanocomposite film, the XPS spectra of the surfaces of these three substrate materials were almost identical. Figure 10 a, Figure 10 d、 Figure 10 g), which indicates that the nanocomposite film can completely cover the substrate material, masking its original elemental distribution characteristics.

[0106] Specifically, a nitrogen (N) signal appeared in the XPS full spectrum on the aluminum substrate, confirming the successful formation of a nanocomposite film on a nitrogen-free substrate. Figure 10 a). Furthermore, the characteristic peaks of LAP in the nanocomposite film (such as those of magnesium, silicon, and sodium) are clearly visible in the XPS spectrum, while the characteristic peak of aluminum disappears. High-resolution spectroscopy of oxygen further confirms this, revealing the presence of Si-O bonds unique to the nanocomposite film, which are absent in the high-resolution spectrum of a blank aluminum substrate. Figure 10 b, Figure 10 c).

[0107] For polyurethane substrates, the XPS full spectrum results were similar to those for aluminum substrates, also showing the distribution of LAP characteristic elements ( Figure 10 d). Characteristic peaks of the Si-O bond in LAP were also observed in the high-resolution spectrum of oxygen. Figure 10 e, Figure 10 f), further confirming the uniform coverage effect of the nanocomposite film. XPS analysis on the silicon substrate also showed a similar trend, with the distribution of characteristic elements in the nanocomposite film overshadowing the elemental signals of the original substrate. Figure 10 g、 Figure 10 h、 Figure 10 i). In summary, these results fully demonstrate that OVA / TA-LAP nanocomposite films can form uniform and continuous coatings on different types of substrate materials, significantly altering the surface chemical composition of the substrates.

[0108] (5) Microstructure of OVA / TA-LAP nanocomposite film

[0109] Figure 11 Scanning electron microscopy (SEM) images of OVA / TA-LAP nanocomposite films on different substrates are presented. Regardless of whether the substrate material is metallic (Al, Ti), polymeric (PU, PVC, PTFE, PS, PMMA, PE, PP, Parafilm), inorganic (Si, Glass), or natural (Paper, Leave, Wood), the OVA / TA-LAP nanocomposite films exhibit high uniformity and density. In the SEM images, the red signal represents the silicon signal detected by energy-dispersive X-ray spectroscopy (EDX). It is clearly observed from the images that silicon is uniformly distributed on the surface of the OVA / TA-LAP nanocomposite films. This observation not only confirms the successful formation of OVA / TA-LAP nanocomposite films on different substrate materials but also further demonstrates their uniformity and density. This uniform distribution is crucial for improving film performance, indicating not only the integrity and continuity of the film at the microscale but also helping to explain its long-term stability and ability to adapt to complex environments in practical applications.

[0110] Of particular note is the ability of natural materials like wood to exhibit complex microstructures and undulations on their surfaces. Even on such complex surfaces, the OVA / TA-LAP nanocomposite film can still uniformly cover the surface, forming a dense membrane. This phenomenon demonstrates that the OVA / TA-LAP nanocomposite film possesses excellent adaptability, flexibility, and covering power, enabling it to form a uniform coating on substrates of various types and complex shapes. This provides a significant advantage in adapting to complex environments during application. Further analysis shows that the surface morphology of the nanocomposite film is consistent across different substrates, exhibiting smooth and continuous characteristics, which is crucial for its reliability and functionality in practical applications. The combined analysis results of SEM and EDX not only validate the successful preparation of the OVA / TA-LAP nanocomposite film but also provide solid experimental evidence for its application on various substrate materials.

[0111] Atomic force microscopy (AFM) was used to further characterize the internal structure of the nanocomposite film. The study showed that the formation of the nanocomposite film was mainly due to the accumulation of OVA / TA-LAP nanoparticles. At low LAP concentrations (2 mg / mL), a large number of nanoscale spherical structures were observed. Figure 12 a); As the LAP concentration increases, the size of nanoparticles in the composite membrane increases ( Figure 12b). This change is attributed to the significant adsorption of OVA-TA by LAP and the stacking of LAP itself. Scratch analysis of the height variation of the nanocomposite film showed that regardless of whether the LAP concentration was 2 mg / mL or 8 mg / mL, the nanocomposite film exhibited good uniformity, with height variations within 30 nm. Figure 12 a', Figure 12 b'). Further magnified observation of the OVA / TA-LAP nanocomposite film (8 mg / mL) clearly revealed the stacking structure of the nanoparticles. Figure 12 (c and c'). Statistical analysis of the nanoparticle sizes revealed that they are mainly distributed at approximately 190 nm, consistent with the results obtained from dynamic light scattering. Analysis of the surface roughness of the nanocomposite film showed that with increasing LAP concentration, the surface roughness of the OVA / TA-LAP nanocomposite film increased from 36.51 nm to 63.93 nm (Table 3). This phenomenon is mainly due to the stacking of LAP, which makes the surface of the nanocomposite film rougher.

[0112] Table 3 Roughness analysis of lithium diatomite nanocomposite films with different concentrations.

[0113] 2 4.14 5.19 36.50 8 6.78 8.62 63.90

[0114] Furthermore, the microstructure of the cross-section of the nanocomposite membrane was observed using SEM. Figure 13 Image a shows a cross-sectional scanning electron microscope (SEM) image of the OVA-LAP composite membrane. The membrane cross-section exhibits a layered structure, indicating a relatively uniform distribution during the preparation process. However, the OVA-LAP composite membrane also contains microscopic cracks and does not form a relatively dense and uniform internal structure. Figure 13 As shown in b, compared with the OVA-LAP composite membrane, the OVA / TA-LAP nanocomposite membrane exhibits a tightly stacked and well-oriented microstructure in its cross-section, with tighter interlayer bonding and a more uniform overall structure. The addition of TA significantly improves the membrane's microstructure, enhancing its compactness and mechanical strength. This structural improvement contributes to increasing the membrane's Young's modulus.

[0115] like Figure 13As shown in Figure c, compared to pure LAP, the broad diffraction peak at 19.65° in the OVA / TA-LAP nanocomposite film represents the inter-chain spacing (0.53 nm) of the β-sheet structure. This result is consistent with the FTIR and CD results, further confirming the change in the secondary structure of OVA (an increase in the β-sheet content). Furthermore, in the 2θ range of 0.5-5°, the weak broad peak of LAP at 1.08° represents its unique arrangement structure, at which point the interlayer spacing between LAP nanosheets is 8.97 nm. In contrast, in the OVA / TA-LAP nanocomposite film, the strong peak at 2θ=0.68° represents the highly ordered oriented arrangement structure of LAP, with an interlayer spacing of 14.94 nm. Figure 13 d). The above results indicate that there is a strong interaction between OVA / TA and LAP, and this interaction results in a well-stacked and highly oriented structure of the OVA / TA-LAP nanocomposite film, which gives it high stability and excellent mechanical properties.

[0116] Furthermore, transmission electron microscopy was used to directly observe the morphological differences between LAP and OVA / TA-LAP. For example... Figure 14 As shown in Figure a, in the presence of OVA / TA, a large amount of OVA / TA is adsorbed on the LAP surface, and its size increases slightly. Conversely, in the absence of OVA / TA, there is no OVA / TA adhesion on its surface, exhibiting a relatively smooth and uniform surface. Figure 14 b). Energy dispersive spectroscopy (EDS) scans of magnified local images of OVA / TA-LAP reveal that the silicon element, unique to LAP, is concentrated at the center of the nanosheet structure (blue signal), while it is surrounded by oxygen elements (red signal). This further confirms that OVA / TA can act as a slurry, adhering to the LAP (bricks and tiles) to form an OVA / TA-LAP nanocomposite. Figure 14 c, 14d).

[0117] In general, similar to common house structures, simple stacks of bricks and tiles have relatively small gaps and poor bonding strength, making the wall prone to collapse under slight external forces. However, when mortar is filled between the bricks and tiles, although the gaps between them widen, the mortar acts as glue, allowing the bricks and tiles to be bonded together more firmly and tightly in a specific arrangement.

[0118] The presence of OVA / TA significantly improves the compactness and interlayer bonding of the nanocomposite membrane, which explains why the OVA / TA-LAP nanocomposite membrane exhibits significant advantages in mechanical properties and structural stability. In the formation of the OVA / TA-LAP nanocomposite membrane, OVA / TA acts as the "slurry," while LAP acts as the "bricks and tiles." OVA / TA is initially adsorbed around the LAP nanosheet structure through electrostatic interactions. Subsequently, during the formation of the nanocomposite membrane, water gradually evaporates from the system, increasing the concentration of the remaining "slurry." The forces between the slurry particles and between the slurry and LAP also gradually increase. This not only promotes the close packing of LAP but also greatly enhances the mechanical strength of the entire nanocomposite membrane.

[0119] (6) Contact angle of OVA / TA-LAP nanocomposite film

[0120] Experiments show that the substrate material without OVA / TA-LAP nanocomposite film coating has a large contact angle, indicating that these materials are inherently hydrophobic. Figure 15 a). After coating with the OVA / TA-LAP nanocomposite film, the contact angles of various substrate materials decreased significantly, indicating that the coating layer increased the hydrophilicity of the surface. Previous studies have shown that TA, due to its large number of hydrophilic groups, exhibits better hydrophilicity compared to the substrate material. Especially on relatively hydrophobic substrate surfaces, the water contact angle is significantly reduced after the OVA / TA-LAP nanocomposite film is formed. Calculations of the contact angles of different substrate surfaces using the θ / 2 method show that the contact angles of the blank group materials are related to the material type. Therefore, the surfaces of different blank group substrate materials all exhibit low hydrophilicity, while their static contact angles show significant differences (…). Figure 15 b). After film formation, the static contact angle of the substrate material decreased significantly. Conversely, once the OVA / TA-LAP nanocomposite film was formed, the contact angles of all substrate material surfaces were nearly uniform (17.71°±2.49°), and both exhibited high hydrophilicity. This indicates that the OVA / TA-LAP nanocomposite film anchored to the material surface exhibits high hydrophilicity and uniformity; regardless of the substrate material, the OVA / TA-LAP nanocomposite film can maintain its surface in a uniform and relatively hydrophilic state. Figure 15 c). Coating with the OVA / TA-LAP nanocomposite film significantly reduced the contact angle of all tested substrate materials, indicating that the nanocomposite film exhibits good hydrophilicity on various material surfaces. This universal coating effect gives the OVA / TA-LAP nanocomposite film broad application potential. LAP, as a reinforcing phase, further improves the stability and uniformity of the film, enabling it to form a stable hydrophilic layer on various substrate surfaces.

[0121] (7) Stability of OVA / TA-LAP nanocomposite film

[0122] To investigate the stability of the OVA / TA-LAP nanocomposite membrane of this invention, its degradation in different solvents was studied. For ease of observation, the OVA / TA-LAP nanocomposite membrane was randomly cut into different shapes to more clearly visualize its degradation in different solvents.

[0123] like Figure 16 As shown in Figure a, the nanocomposite membrane was placed in different organic solvents for a week, and its shape did not show significant changes. This indicates that the nanocomposite membrane can effectively resist corrosion from organic solvents and acids / alkalis. More notably, even with highly corrosive aqua regia, the nanocomposite membrane remained stable. Furthermore, the nanocomposite membrane was removed and dried every other day to analyze its mass change. The mass change of the nanocomposite membrane is shown in Figure a. Figure 16 As shown in b, the mass change of the OVA / TA-LAP nanocomposite membrane remained at approximately 20% over a week. This mass loss was primarily due to the gradual dissolution of glycerol in the nanocomposite membrane in organic solvents or strong acids and bases. Figure 16 c illustrates the stabilizing mechanism of the nanocomposite membrane. The OVA / TA-LAP nanocomposite membrane exhibits minimal changes in appearance and mass in most organic solvents, indicating good solvent stability. This stability is primarily attributed to the synergistic effect between OVA and TA (slurry-like structure) and the reinforcing effect of LAP (brick-and-mortar structure), resulting in excellent stability in organic solvents. Simultaneously, the OVA / TA-LAP nanocomposite membrane maintains good structure and mass in strong acid and alkali solutions, demonstrating a certain degree of chemical resistance. This resistance may be due to the "slurry-brick-and-mortar" structure of the nanocomposite membrane, which allows LAP to be uniformly distributed and oriented within the membrane, while OVA / TA fills the "gaps" and forms a uniform internal structure, hindering the intrusion of various corrosive ions and maintaining the integrity of the nanocomposite membrane structure over a longer period.

[0124] In addition to chemical resistance, the OVA / TA-LAP nanocomposite membrane also exhibits excellent high-temperature resistance. Figure 17 Figure d shows the thermogravimetric curves of the nanocomposite coating films with different lithium diatomite concentrations. Since this nanocomposite film can be formed on a polymer matrix, it can serve as a highly stable film to protect the substrate material from complex environments. In this part of the experiment, the flame-retardant properties of the OVA / TA-LAP nanocomposite film were evaluated using highly flammable paraffin film as the combustion substrate. Figure 17In the horizontal combustion test, the paraffin film in the blank group was ignited within 3 seconds, exhibiting a bright flame and gradually melting and breaking during combustion. However, the paraffin film coated with the OVA / TA-LAP nanocomposite film did not show any combustion within 3 seconds, and the overall appearance of the nanocomposite film did not show any significant change. Figure 17 a). Due to factors such as higher heat transfer efficiency, smoother airflow, faster removal of combustion products, and flame characteristics, vertical combustion is more efficient than horizontal combustion. Therefore, vertical combustion tests are more effective in demonstrating the flame-retardant effect of the OVA / TA-LAP nanocomposite film on the substrate material. Figure 17 b). For example Figure 17 a and Figure 17 As shown in b, the paraffin film in the blank group was easily ignited (< 1 s) and continued to burn, accompanied by the generation of molten droplets and a large amount of smoke, until it was completely burned. However, for the paraffin film coated with OVA / TA-LAP nanocomposite film, no obvious burning phenomenon was observed within 3 s, and the shape of the entire material did not change significantly.

[0125] The OVA / TA-LAP nanocomposite membrane exhibits excellent flexibility and strong interfacial adhesion to the substrate material, enabling it to form a stable and durable protective film on flexible substrates. The highly efficient protective performance of the OVA / TA-LAP nanocomposite membrane, particularly in terms of chemical stability and flame retardancy, is primarily attributed to its unique "slurry-brick" structure. This structure forms a dense protective barrier during combustion, effectively preventing heat transfer and blocking the penetration of oxygen and other combustion-dependent molecules. Specifically, the "slurry-brick" structure of the nanocomposite membrane enhances its overall stability through the formation of interlocking layered arrangements within the membrane. When heated, this structure acts as a physical barrier, significantly reducing the rate of heat transfer to the substrate material. Furthermore, this dense, interlocking structure effectively blocks the entry of oxygen and other combustion-supporting gases, thereby inhibiting the combustion reaction.

[0126] In summary, the OVA / TA-LAP nanocomposite membrane not only exhibits excellent heat shielding during combustion but also provides additional protection through its chemically stable inorganic components (LAP). These inorganic components maintain their structural integrity at high temperatures, further enhancing the overall protective capability of the membrane system. Therefore, this multi-protection mechanism of the OVA / TA-LAP nanocomposite membrane makes it a highly efficient flame-retardant and chemically protective membrane material, suitable for various applications requiring high-performance protection.

[0127] In summary, the ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane and its preparation method provided by this invention can prepare nanocomposite membranes of the required size on demand in an all-aqueous system. The preparation process is green, environmentally friendly, simple, and inexpensive. The prepared nanocomposite membrane exhibits excellent stability, interfacial adhesion, flame retardancy, and chemical corrosion resistance, and can be widely used for surface protection of various substrates such as polymer materials, metal materials, inorganic non-metallic materials, and wood products. It has broad industrial application prospects in flame-retardant coatings and chemical corrosion-resistant protective coatings.

Claims

1. A method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane, characterized in that, The method involves first uniformly dispersing lithium diatomaceous earth using ovalbumin, and then anchoring tannic acid around the lithium diatomaceous earth using the intermolecular interaction between tannic acid and ovalbumin, thereby obtaining a uniformly dispersed ovalbumin / tannic acid-lithium diatomaceous earth composite system; after drying, a stable ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite film can be formed.

2. The method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane as described in claim 1, characterized in that, Includes the following steps: Step 1: Preparation of ovalbumin-lithium diatomaceous earth mixture S1: Prepare an ovalbumin solution by dissolving ovalbumin and glycerol in deionized water; S2: Disperse lithium diatomite in water to prepare lithium diatomite dispersion; S3: Prepare an ovalbumin-lithium diatomaceous earth mixture by mixing the ovalbumin solution with the lithium diatomaceous earth dispersion; stir and mix at room temperature; Step 2: Preparation of tannic acid solution Tannic acid solution is prepared by dissolving tannic acid in water; Step 3: Preparation of ovalbumin / tannic acid-lithium diatomaceous earth mixture The tannic acid solution was added to the ovalbumin-lithium diatomite mixture and stirred at room temperature to prepare an ovalbumin / tannic acid-lithium diatomite mixture. Step 4: Film Formation The ovalbumin / tannic acid-lithium diatomite mixture was dried to obtain an ovalbumin / tannic acid-lithium diatomite nanocomposite membrane.

3. The method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane as described in claim 2, characterized in that, In step one, the concentration of ovalbumin in the ovalbumin solution is 10 mg / mL to 30 mg / mL; the concentration of glycerol in the ovalbumin solution is 10 mg / mL to 30 mg / mL; and the concentration of the lithium diatomaceous earth dispersion is 2 mg / mL to 8 mg / mL.

4. The method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane as described in claim 2, characterized in that, The concentration of the tannic acid solution mentioned in step two is 2 mg / mL to 4 mg / mL.

5. The method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane as described in claim 2, characterized in that, The drying temperature in step four is 30–50°C, and the drying time is 12–24 h.

6. The method for preparing an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane as described in claim 2, characterized in that, In step four, the ovalbumin / tannic acid-lithium diatomaceous earth mixture is dried together with the substrate material to obtain an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane; the substrate material includes polymer materials, metal materials, inorganic non-metallic materials and wood products.

7. A self-supporting ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane, characterized in that, The composite membrane is obtained by the method described in any one of claims 1-5.

8. A substrate material, an ovalbumin / tannic acid-lithium diatomaceous earth nanocomposite membrane, characterized in that, The composite membrane is obtained by the method described in claim 6.

9. The application of the ovalbumin / tannic acid-lithium diatomite nanocomposite membrane according to claim 7 or 8 as a flame-retardant and / or chemically resistant protective membrane material.

10. A flame-retardant and / or chemically resistant protective method, characterized in that, The method includes the step of covering the surface of the substrate to be protected with the ovalbumin / tannic acid-lithium diatomite nanocomposite film as described in claim 7.